2019
DOI: 10.17269/s41997-019-00226-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex workers’ experiences and occupational conditions post-implementation of end-demand criminalization in Metro Vancouver, Canada

Abstract: Objectives In 2014, Canada introduced end-demand criminalization (the Protection of Communities and Exploited Persons Act (PCEPA)), criminalizing purchase of sexual services while leaving the sale of sex legal. We assessed factors correlated with selfreported changes in working conditions post-PCEPA among sex workers (SWs) in Metro Vancouver. Methods Post-PCEPA data for one year were drawn from a community-based cohort of SWs. We analyzed self-reported changes in working conditions among 299 participants who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…In the 5 years since the law's enactment, research from various parts of Canada has reported harms in sex workers' relationships with law enforcement and in their safety as being similar to what was previously experienced under prohibitive sex work legislation [30,82,85,87,88]. One cisgender woman sex worker who predominantly solicited clients in street-based settings said: "Harassing the clients is exactly the same as harassing the women.…”
Section: Box 72 Country Spotlight End-demand Criminalisation: Canadamentioning
confidence: 90%
See 4 more Smart Citations
“…In the 5 years since the law's enactment, research from various parts of Canada has reported harms in sex workers' relationships with law enforcement and in their safety as being similar to what was previously experienced under prohibitive sex work legislation [30,82,85,87,88]. One cisgender woman sex worker who predominantly solicited clients in street-based settings said: "Harassing the clients is exactly the same as harassing the women.…”
Section: Box 72 Country Spotlight End-demand Criminalisation: Canadamentioning
confidence: 90%
“…massage parlours) as well as sex workers who already face high rates of criminalisation (e.g. due to illicit drug use) were most likely to report negative changes after the implementation of the PECPA [82]. These findings highlight that the implementation of end-demand legislation in Canada has resulted in further marginalising the most precarious groups of sex workers.…”
Section: Box 72 Country Spotlight End-demand Criminalisation: Canadamentioning
confidence: 92%
See 3 more Smart Citations